Human-modified landscapes alter mammal resource and habitat use and trophic structure - Magioli, Marcelo; Moreira, Marcelo Zacharias; Batista Fonseca, Renata Cristina [UNESP]; Ribeiro, Milton Cezar [UNESP]; Rodrigues, Marcia Goncalves; Micchi de Barros Ferraz, Katia Maria Paschoaletto (Natl Acad Sciences, 2019)
The broad negative consequences of habitat degradation on biodiversity have been studied, but the complex effects of natural-agricultural landscape matrices remain poorly understood. Here we used stable carbon and nitrogen isotopes to detect changes in mammal resource and habitat use and trophic structure between preserved areas and human-modified landscapes (HMLs) in a biodiversity hot spot in South America. We classified mammals into trophic guilds and compared resource use (in terms of C-3- and C-4-derived carbon), isotopic niches, and trophic structure across the 2 systems. In HMLs, approximately one-third of individuals fed exclusively on items from the agricultural matrix (C-4), while in preserved areas, similar to 68% depended on forest remnant resources (C-3). Herbivores, omnivores, and carnivores were the guilds that most incorporated C-4 carbon in HMLs. Frugivores maintained the same resource use between systems (C-3 resources), while insectivores showed no significant difference. All guilds in HMLs except insectivores presented larger isotopic niches than those in preserved areas. We observed a complex trophic structure in preserved areas, with increasing delta N-15 values from herbivores to insectivores and carnivores, differing from that in HMLs. This difference is partially explained by species loss and turnover and mainly by the behavioral plasticity of resilient species that use nitrogen-enriched food items. We concluded that the landscape cannot be seen as a habitat/nonhabitat dichotomy because the agricultural landscape matrix in HMLs provides mammal habitat and opportunities for food acquisition. Thus, favorable management of the agricultural matrix and slowing the conversion of forests to agriculture are important for conservation in this region.
Keywords: stable isotope analysis; landscape matrix; agriculture; diet; noninvasive sampling